Penetrating foreign body in the neck with traversing up to spinous process: An unusual case report - Gautam, Harendra Kumar (Indian Journal of Case Reports, 2020)
Penetrating neck injuries are potentially dangerous and necessitate emergency treatment. Early diagnosis and removal of a foreign body is imperative to prevent further complications. We report a case of an 11-year-old male who presented to the otolaryngology department with the history of penetrating neck injury with a metallic wire. On examination, a foreign body in the left side of the neck at the level of hyoid bone was found. On contrast-enhanced computed tomography, a metallic linear foreign body in the left side of the neck was seen passing obliquely at the level of hyoid bone into muscle plane and was traversing up to posterior spinous process. The foreign body was explored and removed under general anesthesia by an open lateral cervical approach. The patient’s post-operative recovery was uneventful. An open surgical approach in cases of sharp metallic foreign bodies impacted deep in the neck can be life-threatening with high morbidity due to the extensive dissection required and the proximity to vital structures.